PENGARUH TAKARAN PUPUK FOSFAT DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG SEMI (Zea mays L.) VARIETAS HIBRIDA - kasno, kasno; Faqih , Achmad; Jaenudin, Amran (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2021)
This experiment aims to determine the effect of phosphate fertilizer dosage and planting distance on the growth and yield of semi-corn (Zea mays L.) Hybrid CPI-2 variety. The experiment was conducted in Mekarjaya Village, Gantar District, Indramayu Regency, West Java. The research was carried out from March to June 2020. The location is situated at an elevation of 493 meters above sea level (masl), with soil types classified as Latosol and Regosol associations, and belongs to the C (moderately wet) rainfall type. The experimental method used was an experimental design with a Randomized Block Design (RBD) in a factorial pattern, with treatments consisting of two factors repeated twice. The first factor was phosphate fertilizer, with four levels: 18 kg P₂O₅/ha (50 kg SP-36/ha), 36 kg P₂O₅/ha (100 kg SP-36/ha), 54 kg P₂O₅/ha (150 kg SP-36/ha), and 72 kg P₂O₅/ha (200 kg SP-36/ha). The second factor is the planting distance, which consists of four levels: 60 x 10 cm, 60 x 15 cm, 60 x 20 cm, and 60 x 25 cm. The main observation data were analyzed using linear statistical models, analysis of variance, and Scott-Knot cluster analysis. The experimental results show: (1) The combination of phosphate fertilizer treatment and planting distance has a significant effect on the number of cobs per plot and the weight of cobs without husks per plot. It does not significantly affect plant height, number of leaves per plant, stem diameter, number of cobs per plant, cob length without husk, cob diameter without husk, and cob weight without husk per plant. (2) The combination of 72 kg P₂O₅/ha of phosphate fertilizer and a planting distance of 60x10 cm showed the best effect on cob weight without husk per plot, yielding 13.7 kg/plot or equivalent to 19.57 tons/ha.